"The Rest of my Childhood was Lost": Canadian Children and Adolescents' Experiences Navigating Inflammatory Bowel Disease. (January 2022) - Barned, Claudia; Fabricius, Alexis; Stintzi, Alain; Mack, David R; O'Doherty, Kieran C
Children and adolescents with Inflammatory Bowel Disease (IBD) face significant and unique challenges related to their condition. The aim of this study was to better understand some of these challenges, and to explore how Canadian youth respond to them. We interviewed 25 pediatric patients with IBD, ranging in age from 10–17, to find out about their illness experiences. Using a thematic analysis, we discerned three themes: challenges related to diagnosis, making sense of change, and navigating sociability . Taken together, they paint a picture of young people facing great uncertainty prior to diagnosis, pronounced changes to selfhood as they make lifestyle adjustments, and facing difficulties with the implications of reduced sociability because of their disease. We conclude by providing recommendations for the development of resources aimed at helping newly diagnosed pediatric patients navigate these issues.